COGNITIVE ASPECTS OF SCHIZOPHRENIA – A NARRATIVE REVIEW - Arsic, Sladjana D; Djordjevic, Jelena; Pavlovic, Dragan; Pavlovic, Aleksandra (PONS - medicinski časopis, 2022)
Cognitive dysfunction has been recognized as a key aspect of schizophrenia evident even during remission of symptoms. During the previous decade, interest in cognitive deficits has increased due to the recognition of their key importance for the functional outcome and degree of social adaptation. Prominent cognitive deficits are disorders of memory, attention and executive functions that manifest themselves as a disorder of verbal fluency, problems with serial learning, difficulty in problem solving, and disturbance of executive functions. The observed cognitive deficit is attributed to the dysfunction of cortical-cerebellar-talamic cortical circuits. Social cognition is the ability to construct an image of relationships between oneself and others and the ability to use flexible mental constructs as a guide to social interactions. The data from previous studies strongly support the association of neurocognitive and sociocognitive deficits with the performance of independent functioning and quality of life, emphasizing the need for prevention and treatment of cognitive deficits.